Light-activated, bioadhesive, poly(2-hydroxyethyl methacrylate) brush coatings - Wang, Jian (2020)
Rapid adhesion between tissue and synthetic materials is relevant to accelerate wound healing and to facilitate the integration of implantable medical devices. Most frequently, tissue adhesives are applied as a gel or a liquid formulation. This manuscript presents an alternative approach to mediate adhesion between synthetic surfaces and tissue. The strategy presented here is based on the modification of the surface of interest with a thin polymer film that can be transformed on-demand, using UV-light as a trigger, from a nonadhesive into a reactive and tissue adhesive state. As a first proof-of-concept, the feasibility of two photoreactive, thin polymer film platforms has been explored. Both of these films, colloquially referred to as polymer brushes, have been prepared using surface-initiated atom transfer radical polymerization (SI-ATRP) of 2-hydroxyethyl methacrylate (HEMA). In the first part of this study, it is shown that direct UV-light irradiation of PHEMA brushes generates tissue-reactive aldehyde groups and facilitates adhesion to meniscus tissue. While this strategy is very straightforward from an experimental point of view, a main drawback is that the generation of the tissue reactive aldehyde groups uses the 250 nm wavelength region of the UV spectrum, which simultaneously leads to extensive photodegradation of the polymer brush. The second part of this report outlines the synthesis of PHEMA brushes that are modified with 4-[3-(trifluoromethyl)-3H-diazirin-3-yl]benzoic acid (TFMDA) moieties. UV-irradiation of the TFMDA containing brushes transforms the diazirine moieties into reactive carbenes that can insert into C-H, N-H, and O-H bonds and mediate the formation of covalent bonds between the brush surface and meniscus tissue. The advantage of the TFMDA-modified polymer brushes is that these can be activated with 365 nm wavelength UV light, which does not cause photodegradation of the polymer films. While the work presented in this manuscript has used silicon wafers and fused silica substrates as a first proof-of-concept, the versatility of SI-ATRP should enable the application of this strategy to a broad range of biomedically relevant surfaces.